Diagnostic performance of FibroTest, SteatoTest and ActiTest in patients with NAFLD using the SAF score as histological reference. Issue 8 (23rd August 2016) - Munteanu, M.; Tiniakos, D.; Anstee, Q.; Charlotte, F.; Marchesini, G.; Bugianesi, E.; Trauner, M.; Romero Gomez, M.; Oliveira, C.; Day, C.; Dufour, J.‐F.; Bellentani, S.; et al.
Summary: Background: Blood tests of liver injury are less well validated in non‐alcoholic fatty liver disease (NAFLD) than in patients with chronic viral hepatitis. Aims: To improve the validation of three blood tests used in NAFLD patients, FibroTest for fibrosis staging, SteatoTest for steatosis grading and ActiTest for inflammation activity grading. Methods: We pre‐included new NAFLD patients with biopsy and blood tests from a single‐centre cohort (FibroFrance) and from the multicentre FLIP consortium. Contemporaneous biopsies were blindly assessed using the new steatosis, activity and fibrosis (SAF) score, which provides a reliable and reproducible diagnosis and grading/staging of the three elementary features of NAFLD (steatosis, inflammatory activity) and fibrosis with reduced interobserver variability. We used nonbinary‐ROC (NonBinAUROC) as the main endpoint to prevent spectrum effect and multiple testing. Results: A total of 600 patients with reliable tests and biopsies were included. The mean NonBinAUROCs (95% CI) of tests were all significant ( P < 0.0001): 0.878 (0.864–0.892) for FibroTest and fibrosis stages, 0.846 (0.830–0.862) for ActiTest and activity grades, and 0.822 (0.804–0.840) for SteatoTest and steatosis grades. FibroTest had a higher NonBinAUROC than BARD (0.836; 0.820–0.852; P = 0.0001), FIB4 (0.845; 0.829–0.861; P = 0.007) but not significantly different than the NAFLD score (0.866; 0.850–0.882; P = 0.26). FibroTest had a significant difference in median values between adjacent stage F2 and stage F1 contrarily to BARD, FIB4 and NAFLD scores (Bonferroni test P < 0.05). Conclusions: In patients with NAFLD, SteatoTest, ActiTest and FibroTest are non‐invasive tests that offer an alternative to biopsy, and they correlate with the simple grading/staging of the SAF scoring system across the three elementary features of NAFLD: steatosis, inflammatory activity and fibrosis.